2020
DOI: 10.3390/ijerph17207527
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Compare the Delivery of Psychiatric Care for People with Treatment-Resistant Schizophrenia

Abstract: Introduction: Community services are gaining ground when it comes to attention to patients with psychiatric diseases. Regarding patients with treatment-resistant schizophrenia (TRS), the use of information and communication technology (ICT) could help to shift the focus from hospital-centered attention to community services. This study compares the differences in mental health services provided for patients with TRS in Budapest (Hungary), Tel-Aviv (Israel) and Catalonia (Spain) by means of a method for the qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this sense, CRS could include the option of low‐intensity entailment with activities focusing on specific needs. Some profiles of patients would benefit more of a low‐intensity entailment, which has not been yet delivered in several countries (Alonso‐Solís et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this sense, CRS could include the option of low‐intensity entailment with activities focusing on specific needs. Some profiles of patients would benefit more of a low‐intensity entailment, which has not been yet delivered in several countries (Alonso‐Solís et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some profiles of patients would benefit more of a low-intensity entailment, which has not been yet delivered in several countries (Alonso-Solís et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The REFINEMENT glossary provides consensus-based operational definitions of the basic terms relevant for the disambiguation process in health services. DESDE has been used for the comparison of mental health service typologies across countries (Alonso-Solís et al ., 2020 ), analysis of disambiguation of complex terms in health care, such as psychotherapy, (Castelpietra et al ., 2021 ) and for the content analysis of the national classifications system compared to an international standard (Rosen et al ., 2020 ). Previous research has shown that the DESDE instrument scores high in feasibility, consistency, inter-rater reliability as well as face, content and construct validity (Salvador-Carulla et al ., 2013 ), as well as its applicability in health economics studies (Romero-Lopez-Alberca et al ., 2019 ).…”
Section: Methodsmentioning
confidence: 99%